Epidemiologic surveillance of tuberculosis in prisons of Espírito Santo - Macedo, Laylla Ribeiro (2014)
Objective: To identify the epidemiological profile of tuberculosis cases diagnosed during the period from July 2009 to July 2010 in the inmate population of prison facilities situated in the state of Espírito Santo (ES). Methods: Epidemiologic, descriptive and retrospective survey comprising the diagnosed tuberculosis cases in the 27 prison units in ES administered by the State Secretariat of Justice (Secretaria de Estado da Justiça - SEJUS) during the studied period. The data was collected from the review of the standard tuberculosis monitoring records, when the population was characterized by the variables: gender, age range, form of tuberculosis, outcome of the case and location. Descriptive statistics was used by means of tables and graphics. Results: 167 tuberculosis cases were observed (incidence rate of 1,962.6 per 100 thousand prisoners). Male gender had higher number of patients, as well as the 25 to 36 age group and the pulmonary clinical form. On the cases outcome, it is highlighted that 167 (65.3) patients were discharged after being cured and two patients died during the period, the rate of tuberculosis mortality being 11.7 per 100,000 prisoners. The highest tuberculosis incidence was found in patients in prison units of the metropolitan region and a small number of cases occurred in other locations outside the prisons facilities. Conclusion: Cases were mainly male, aged 26 to 35, carriers of the pulmonary form of tuberculosis, coming from the metropolitan region of the state and having discharge/healing as the outcome. doi:10.5020/18061230.2013.p216